A Comparison Study Using Netflix and Joox in Listening Comprehension for Senior High Students - Ryzky Dwy Putry Ananda; Saiful Saiful; Muh. Arief Muhsin (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
The objective of the research is to analyze the effect of Netflix and JOOX as a media in teaching listening comprehension. This research consisted of two variables. The researcher used independent and dependent variable. The independent variable in this research are Netflix and JOOX. And the dependent variable in this research is teaching listening. The population of the research was the second grade students of SMA Muhammadiyah 1 Unismuh Makassar consisted of 22 students from 2 classes, XI IPA I and XI IPS I. The result of the research showed the comparison using Netflix and JOOX as a media in teaching listening, XI IPA I used Netflix and XI IPS I used JOOX. In XI IPS I class, before the treatment, the mean score of students’ pre-test (61.81). After the treatment, the mean score of students’ post-test was (69.09). The result showed the improvement of students’ listening achievement of using JOOX as a media in teaching listening was increased (7.27%). And in XI IPA I class, before the treatment the mean score of students’ pre-test was (63.63). And after the treatment the mean score of students’ post-test was (83.15). The result also showed the improvement of students’ listening achievement of using Netflix as a media in teaching listening was increased (19.54%). It is proved that both of the media can increase the students’ achievement in listening comprehension. The researcher did a homogeiny, validity, reliability and hypothesis testing in this research. This research are considered to be homogeiny. three question items is valid while the other two are invalid and it is affect the data to be unreliable. The hypothesis testing shows that the students’ listening achievement using Netflix and JOOX is increased after the treatment was given.